1997
DOI: 10.1002/(sici)1096-9071(199706)52:2<121::aid-jmv1>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coxsackie B Virus RNA sequences in whole blood samples from adult patients at the onset of type I diabetes mellitus

Abstract: Enteroviruses may be linked to insulin-dependent diabetes mellitus (IDDM). The prevalence of enteroviral (EV) infection at onset of adult IDDM was investigated by detection of specific EV sequences in peripheral blood using a reverse transcription and a seminested polymerase chain reaction (seminested RT-PCR). EDTA-treated whole blood samples taken from 12 newly diagnosed IDDM patients with ketosis or ketoacidosis were examined. The comparison groups were 12 adult patients suffering from metabolic decompensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 25 publications
9
83
0
Order By: Relevance
“…The figure for positivity rose to 37% in children of 3 years of age or younger. These results have been confirmed in a number of other studies in France [30], Sweden [31,32] and in Australia [33]. In the results from Sweden and France, whole blood was the starting point for the work and the percentage positivity rose considerably (Table 2).…”
Section: Coxsackie B Virusessupporting
confidence: 63%
See 2 more Smart Citations
“…The figure for positivity rose to 37% in children of 3 years of age or younger. These results have been confirmed in a number of other studies in France [30], Sweden [31,32] and in Australia [33]. In the results from Sweden and France, whole blood was the starting point for the work and the percentage positivity rose considerably (Table 2).…”
Section: Coxsackie B Virusessupporting
confidence: 63%
“…In one set of results using PCR methodology, it has been shown that positivity for enteroviruses was quite commonly present in adult insulin-dependent diabetic patients at onset [30]. In a small number of patients, previously diagnosed with insulin dependent diabetes, enterovirus sequences could also be detected, raising the possibility of a continuing infection.…”
Section: Significance Of Tests To Detect Virusessupporting
confidence: 55%
See 1 more Smart Citation
“…Much of the evidence is circumstantial [1] but includes observations that antibodies against common Coxsackie B enteroviruses (CVB) and enteroviral RNA occur more frequently in the circulation of recent-onset type 1 diabetes patients than in controls [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, CVB genome was detected in five out of 12 (42%) newly diagnosed T1D patients and in one of 12 (8%) patients during the course of the disease. By contrast, none of 12 T2D patients and none of 15 healthy adults had enterovirus sequences in their blood [43]. The CVB4 strain E2 is able to induce a persistent infection of human islet b cells [44], whereas a new isolated CVB4 variant, VD2921, causes a persistent infection of islet b cells with a consequent disturbance of proinsulin synthesis and insulin secretion [45].…”
Section: Environmental Factorsmentioning
confidence: 97%